2020
DOI: 10.1097/md.0000000000019027
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in National Institute of Health trauma research funding

Abstract: To evaluate disparities in the National Institute of Health (NIH) trauma research funding. Traumatic injury has increased in both prevalence and cost over the last decade. In the event of a traumatic injury, patients in the United States (US) rely on the trauma system to provide high-quality care. The current trauma research funding is not commensurate with the extent of the burden of trauma on the US population. In this qualitative study, the National Institutes of Health's Estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Another hypothesis may be a decreasing interest of urologists for renal trauma care with the increasing role of nonoperative management. Finally, the lack of funding for trauma research and lack of interest of many international peer-reviewed urology journals for renal trauma may slow down the spread and permeation of evidence in the urologic community [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis may be a decreasing interest of urologists for renal trauma care with the increasing role of nonoperative management. Finally, the lack of funding for trauma research and lack of interest of many international peer-reviewed urology journals for renal trauma may slow down the spread and permeation of evidence in the urologic community [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Questions from Round 0 were compiled by the investigator team and loaded into Surveylet for Round 1, during which participants were asked to rate the priority of each research question on a 9-point Likert scale (1, low priority; 9, high priority). In Rounds 2 and 3, participants received numerical and graphical feedback based on the aggregated responses of other survey participants and could change their ratings in an effort to reach consensus regarding each question's priority as low, 1-3 medium, [4][5][6] or high. [7][8][9] Questions that reached consensus, defined as 60% agreement, were removed from subsequent rounds.…”
Section: Internet-based Delphi Methodologymentioning
confidence: 99%
“…Comparatively, the National Institutes of Health spent an estimated $6.3 billion on cancer research in the same year. 4 Pediatric trauma, in particular, remains underfunded at the federal level. For example, a recent study indicated that firearm injury, the second leading cause of death among children and adolescents, received $597 per death in research grants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By way of example, a recent study by Dowd et al found that the National Institute of General Medical Science (NIGMS) provided the largest funding to trauma research. The authors concluded that an established and well-funded institute offers more resources that could be utilized by PIs pursuing trauma research compared to starting a new, smaller institute solely focused in this area [ 4 ]. Furthermore, implemented in 2008 at the request of Congress to address a more transparent method of reporting the relationship between NIH’s research portfolio and public health needs, Research Condition and Disease Categorization (RCDC) was created.…”
Section: Introductionmentioning
confidence: 99%